New Ru(II)/Os(II)-polypyridyl complexes for coupling to TiO2 surfaces through acetylacetone functionality and studies on interfacial electron-transfer dynamics - Banerjee, Tanmay; Biswas, Abul Kalam; Sahu, Tuhin Subhra; Ganguly, Bishwajit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Transactions, 2014)
New Ru(II)- and Os(II)-polypyridyl complexes have been synthesized with pendant acetylacetone (acac) functionality for anchoring on nanoparticulate TiO2 surfaces with a goal of developing an alternate sensitizer that could be utilized for designing an efficient dye-sensitized solar cell (DSSC). Time-resolved transient absorption spectroscopic studies in the femtosecond time domain have been carried out. The charge recombination rates are observed to be very slow, compared with those for strongly coupled dye molecules having catechol as the anchoring functionality. The results of such studies reveal that electron-injection rates from the metal complex-based LUMO to the conduction band of TiO2 are faster than one would expect for an analogous complex in which the chromophoric core and the anchoring moiety are separated with multiple saturated C-C linkages. Such an observation is rationalized based on computational studies, and a relatively smaller spatial distance between the dye LUMO and the TiO2 surface accounted for this. Results of this study are compared with those for analogous complexes having a gem-dicarboxy group as the anchoring functionality for covalent binding to the TiO2 surface to compare the role of binding functionalities on electron-transfer dynamics.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.